Jonas Mekas. Conversations with Artists. Movie Journal Columns 1961-1975. - Mekas, Jonas (Leipzig : Spector Books, 2018)
Hill, Jerome ; De Seta, Vittorio ; Markopoulos, Gregory ; De Hirch, Storm ; Brigante, Louis ; Smith, Jack ; Jacobs, Ken ; Warhol, Andy ; Papatakis, Nico ; Levine, Naomi ; Vanderbeek, Stan ; Mead, Taylor ; Oldenburg, Claes ; Conrad, tony ; Kubelka, peter ; Rubin, barbara ; Dworkin, Andrea ; Langheld, Gretchen ; Snow, Michael ; Varda, Agnès ; Sontag, Susan ; Nordstrom, Kristina ; Rainer, yvonne ; Kaplan, Nelly ; Karina, Anna
verzameling van interviews met filmmakers
boek
Keywords: Mekas, Jonas